Development of a new class of zero cross correlation codes for optical CDMA systems - Mohd Rashidi Bin Che Beson (School of Computer and Communication Engineering, 2011)
Presented a method for development of new class of optical code for Optical Code Division Multiple Access (OCDMA) system using Spectral Amplitude Coding.